2023
DOI: 10.1097/jfn.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

Forensic Nurses' Understanding of Emergency Contraception Mechanisms

Abstract: Background An estimated 25,000 pregnancies result from sexual assault in the United States annually. Numerous professional healthcare organizations endorse offering emergency contraception (EC) as an integrated aspect of post-sexual-assault care. Lack of knowledge surrounding EC's mechanism of action, including misinterpreting ECs as abortifacients, might restrict patient access to this important healthcare option. Purpose We evaluated sexual assault nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
(30 reference statements)
0
10
0
Order By: Relevance
“…A 2023 survey revealed that 16.8% of forensic emergency department nurses thought oral LNG EC could disrupt an established pregnancy, and 21.4% thought the same for UPA. 34 Ensuring that patients understand the difference between EC and pregnancy termination may help them make choices that align with personal views. If a pregnancy occurs after an IUD placement, the standard of care is to remove the IUD and counsel about options.…”
Section: Counselingmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2023 survey revealed that 16.8% of forensic emergency department nurses thought oral LNG EC could disrupt an established pregnancy, and 21.4% thought the same for UPA. 34 Ensuring that patients understand the difference between EC and pregnancy termination may help them make choices that align with personal views. If a pregnancy occurs after an IUD placement, the standard of care is to remove the IUD and counsel about options.…”
Section: Counselingmentioning
confidence: 99%
“…Unfortunately, the distinction between EC and abortion care is not always perceived by patients or health care providers. A 2023 survey revealed that 16.8% of forensic emergency department nurses thought oral LNG EC could disrupt an established pregnancy, and 21.4% thought the same for UPA 34. Ensuring that patients understand the difference between EC and pregnancy termination may help them make choices that align with personal views.…”
Section: Counselingmentioning
confidence: 99%
“…An overview of our screening process is presented in (Fig 1). The final sample consisted predominantly of cross-sectional (n = 6) [25,27,29,31,32,34], modeling (n = 5) [23,24,26,30,35], and observational (n = 4) study designs [19][20][21][22], along with was one retrospective chart review [18], one NLP-based study [28], and one commentary [33] (Table 2).…”
Section: Sample and Article Characteristicsmentioning
confidence: 99%
“…Seven studies (38.9%) in our sample discussed contraception (Table 2). [15][16][17][18][19][20]31 After Dobbs, we observed an increase in the demand for PCs. Notably, there was an increase in the number of Google searches for vasectomies immediately after Dobbs on June 24, 2022, as well as to a smaller extent immediately after the U.S. Supreme Court's draft of Dobbs v. Jackson was leaked on May 2, 2022.…”
Section: Contraceptionmentioning
confidence: 99%
“…31 Several nurses cited concerns about current or legal restrictions around EC prescribing after Dobbs (e.g., fear of prosecution). 31 Additionally, the demand for other contraceptives increased after Dobbs (Table 2). The number of Google searches for "IUD", "birth control pill", and "condom" similarly spiked after Dobbs, albeit to a lower extent than PCs and ECs.…”
Section: Contraceptionmentioning
confidence: 99%